Highly flexible inverted-quantum-dot light-emitting diodes on elastic polyurethane substrates - Kim, Hong Hee; Shim, Jae Won; You, Young-Jun; Lee, Yeon Ju; Park, Cheolmin; Hwang, Do Kyung; Choi, Won Kook (Royal Society of Chemistry, 2017)
Fabrication of highly flexible, inverted, indium tin oxide (ITO)-free top-emitting quantum-dot light-emitting diodes (QDLEDs) on elastic polyurethane (PU) substrates is reported here. To cope with the irregular surfaces of the PU substrate, polyvinyl alcohol (PVA) is used as a buffer layer. By adopting the PVA buffer layer, we demonstrate red-color and green-color top-emitting QDLEDs that show turn-on voltages from 4.0 V to 4.5 V, and maximum luminance values of 1200 cd m−2 (red) and 4800 cd m−2 (green). In addition, when the QDLEDs are stuck on the curved surfaces (vials and a tumbler), the devices still exhibit a clear light emission. These highly flexible QDLEDs can pave the way for further development of next-generation wearable or attachable displays, or solid-state lighting.